Surveillance of health-care associated infections in an intensive care unit at a tertiary care hospital in Central India - Lohiya, Ruchita; Deotale, Vijayshri (German Medical Science GMS Publishing House, 2023)
Introduction: Because the risk of health-care associated infections (HAIs) is high in intensive care units, and HAIs are one of the causes of morbidity and mortality and affects the overall quality of health care, the continuous monitoring of HAIs in intensive care patients is essential.Aim and objectives: This descriptive cross-sectional study was carried out over a period of five years in a tertiary-care teaching hospital. The aim of the study was to investigate the main and specific types of health-care associated Infections and determine the microbiological profile and antimicrobial susceptibility rates of isolates in patients with HAI.Methods: The active surveillance method was used to detect HAIs in patients who spent over 48 hr in a targeted ICU. Patients with blood stream infections (BSI), central line-associated bloodstream infection (CLABSI), catheter-associated urinary tract infections (CAUTI) and ventilator-associated events (VAE) were included in the study. HAI were diagnosed based on the Centre for Disease Control (CDC)'s National Healthcare Safety Network (NHSN) updated definitions of HAIs.Results: A total of 121,051 patient days, including 7,989 central line days, 64,557 urinary catheter days, and 18,443 ventilator days, were recorded in the study population and 832 HAIs were diagnosed (incidence rate 6.9%). The overall rates of BSI, CLABSI, CAUTI and possible ventilator-associated pneumonia (p-VAP) were 3.7, 10.6, 2.1 and 13.4/1,000 device days, respectively. The most common organism isolated from BSI was (n=322, 29%), followed by 225 (n=225, 20.3%). 79.8% of strains were resistant to imipenem, 77.1% to ciprofloxacin and 76.4% to ampicillin. The most common organisms isolated from CAUTI were non-albicans species (n=38, 18%), followed by and spp (each n=33, each 15.7%). Conclusions: A trend of increasing resistance of to carbapenems was observed. Risk factor analysis showed invasive procedures during sepsis and organophosphorous poisoning as significant factors.